Arthur Johnson Memorial Library : Then and Now (Raton, NM Library in house, 1974)
A one page description of the establishment and history of the Arthur Johnson Memorial Library up to 1974.
Information comes from a typed letter dated 1974
Master list item #: 13
File location is in the Raton File Cabinet drawer 3
Keywords: Shuler, J. J. (Dr.) -- Raton, New Mexico; Shuler, Evlyn -- Librarian -- Raton, New Mexico; Cole, Myrtle -- Librarian -- Raton, New Mexico; Library. -- Raton, New Mexico; City Government -- Raton, New Mexico; Arthur Johnson Memorial Library; History -- Raton, New Mexico